Collagenous Gastritis in Children: Incidence, Disease Course, and Associations With Autoimmunity and Inflammatory Markers. Issue 8 (3rd August 2020) - Käppi, Timo; Wanders, Alkwin; Wolving, Mats; Lingblom, Christine; Davidsson Bården, Birgitta; Arkel, Rikard; Hätting, Josefine; Anderzén, Johan; Wennerås, Christine; Saalman, Robert
Abstract : INTRODUCTION: Collagenous gastritis (CG), a rare disorder of unknown etiology, has been postulated to have immune-mediated mechanisms. We investigated (i) the incidence and prevalence of CG in a pediatric population; (ii) the clinical, endoscopic, and histologic characteristics of childhood-onset CG; and (iii) the evidence for autoimmunity and/or inflammatory activity in these patients. METHODS: Clinical, endoscopic, and histologic data were reviewed longitudinally in a population-based Swedish cohort of 15 patients with childhood-onset CG diagnosed in the period 2008–2019. A set of 11 autoantibodies, 4 blood inflammatory biomarkers, and the human leukocyte antigen DQ2/DQ8 genotype was analyzed cross-sectionally. RESULTS: The incidence rate of childhood-onset CG was 0.25/100, 000 person-years, with an incidence rate ratio of girls to boys of 4.2 (95% confidence interval, 1.2–15). The prevalence of CG was 2.1/100, 000 in children aged younger than 18 years. The endoscopic and histologic findings remained pathologic in all the examined patients during a median follow-up of 4.4 years. Many patients had heredity for autoimmune disorders (47%) and/or tested positive for autoantibodies (40%) or human leukocyte antigen DQ2/DQ8 (53%). No associated autoimmune comorbidities were observed. The serum levels of calprotectin and amyloid A were increased in 10/15 (67%) and 5/15 (33%) of the patients, respectively, whereas plasma C-reactive protein levels were normal in all, but 1 patient. DISCUSSION: The results indicate that childhood-onset CG is rare and has a chronic disease course. Although signs of autoimmune predisposition are frequent, early development of autoimmune comorbidities seems seldom. Serum calprotectin and amyloid A represent novel candidate biomarkers of inflammatory activity in CG (see Visual Abstract, Supplementary Digital Content 4, http://links.lww.com/CTG/A349 ).